IoT technologies for tackling COVID-19 in Malaysia and worldwide: Challenges, recommendations, and proposed framework - Al-Ogaili A.S.; Alhasan A.; Ramasamy A.; Marsadek M.B.; Hashim T.J.T.; Al-Sharaa A.; Aadam M.B.; Audah L. (Tech Science Press, 2023)
Health care; Network security; Service industry; Conceptual frameworks; Global public health; Healthcare delivery; Healthcare sectors; Internet of thing (IOT); Surveillance networks; Thermal detection; Tracking and tracing; Internet of things